Treatment of locally advanced cervical cancer in a patient with a bicornuate uterus with MRI-guided intracavitary/interstitial brachytherapy - Fabian, Denise (J Contemp Brachytherapy, 2019)
PURPOSE: Definitive treatment for locally advanced cervical cancer (LACC) includes external beam radiation therapy (EBRT) with concurrent cisplatin and brachytherapy. Image-guided intracavitary brachytherapy utilizes CT and/or MRI for target and organ at risk delineation and has been shown to improve local control rates and decrease toxicity. Hybrid intracavitary/interstitial applicators can be used to improve tumor coverage in certain cases. We describe the use of combined intracavitary/interstitial brachytherapy to treat a cervical cancer patient with a bicornuate uterus. CASE PRESENTATION: A 30-year-old female with bicornuate uterus and FIGO IB2 adenocarcinoma of the cervix was treated with 45 Gy of EBRT to the pelvis with concurrent weekly cisplatin. An examination after EBRT demonstrated a persistent bulky tumor covering most of the cervix. Brachytherapy was delivered via a combined intracavitary/interstitial approach, using a tandem and ring applicator and an interstitial needle. The placement of the tandem was alternated between uterine cornua with each fraction, and the interstitial needle was placed on the side opposite the tandem. CT and MRI were obtained with each fraction. The patient completed the treatment without complications. Three-month restaging PET-CT showed significant interval improvement in the cervix, with a complete clinical response on physical examination. The patient is without evidence of disease 18 months after the treatment. CONCLUSIONS: We found that the use of the hybrid applicator allowed for adequate target coverage in a patient with unusual anatomy. The patient tolerated treatment well and demonstrated favorable response on follow-up exam and imaging. The long-term curative result needs to be further evaluated.